The Impact Of Open Innovation And Knowledge Management On Sme Performance In Yogyakarta - Reza Edwin Akbar; Arif Hartono (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2024)
This research examines the impact of knowledge management, open innovation, and innovation capabilities on the performance of SMEs in the Special Region of Yogyakarta. Although previous studies on open innovation in the Indonesian context have been conducted, specific results from this region still need to be included, and certain variables related to performance improvement in SMEs still need to be explored. Therefore, this study seeks to address these gaps, with 202 respondents contributing to the research. Data analysis was conducted using SPSS and PLS-SEM with the SmartPLS tool. The findings indicate that the variables of knowledge management, open innovation, and innovation capabilities have a positive impact on SME performance. This research aims to enrich the literature on open innovation and SME performance. The study also provides valuable insights for business practitioners and stakeholders on how to implement these variables to enhance business or company performance.